Rapid serogroup classification of the footrot pathogen Dichelobacter nodosus using multiplex qPCR of lesion samples from sheep in the Netherlands - Duim, Birgitta; Dekker, Niels; Everts, Reinard R.; Groenevelt, Margit; Hoogeveen, Joost; Timmerman, Arjen; Zweerus, Heleen; Broekhuizen-Stins, Marian J.; Mokbel, Mohammad; Dhungyel, Om P. (Frontiers in Veterinary Science, 2026)
Dichelobacter nodosus (D. nodosus) is the pathogen responsible for causing footrot in sheep and goats, which poses significant challenges to animal health and welfare. D. nodosus is classified into 10 different serogroups (A–I and M) based on the genetic variation of this fimbrial (fimA) gene. These fimbriae are immunogenic and play an important role in virulence, making serotyping of these fimbriae valuable for identification and vaccine development. In this study, three multiplex quantitative polymerase chain reaction (qPCR) assays, targeting the most commonly prevalent nine serogroups (ABC, DEF, and GHI), were studied for the detection of serogroups in foot swab samples collected from Dutch sheep farms. A total of 147 samples tested positive for D. nodosus using pnpA qPCR, and 144 (98%) samples exhibited a serogroup using qPCR. The multiplex qPCRs detected significantly more serogroups than conventional serogroup PCRs and detected more than one serogroup in a swab. In 46 samples (31%, 46/147), two to five different serogroups were identified from a single swab sample. In three samples, no serogroup was identified, likely due to sequence variation in the fimA gene in these samples. These direct multiplex qPCR tests provide faster, more sensitive, and accurate testing for the direct classification and quantification of D. nodosus serogroups for studying the epidemiology of footrot and for the formulation of serogroup-specific targeted vaccination strategies for prevention, control, and treatment of footrot.